A historical laboratory in Rome (Italian Journal of Public Health, 2010)
Visitors who climb the austere stairs of the Giuseppe Sanarelli Institute, headquarters of the Public Health Sciences Department, in the University La Sapienza of Rome, may experience a strange feeling: the steps follow one another identically, yet each seems taller and more difficult than the last. It is as if, with every step, time reveals its stories, experiences; ever larger and harder to sustain. Following the corridor it is impossible not to pause and reflect upon the displays of memories and details belonging to the past. There is a constant sensation, almost tangible: it is as if each of the objects, so dense with memories, want to take you on a fantastic voyage to another time and place. Objects made of wood, copper and other materials that come from the past, filled with the scent of a world that no longer exists.